Campur Kode Dalam Percakapan Komunitas Mahasiswa Di Asrama Lamandau Dan Implikasinya Terhadap Pembelajaran Cerpen Siswa Sma Kelas XI - Vidella Maro Tohang; Petrus Poerwadi; Albertus Purwaka; Lazarus Linarto; Misnawati Misnawati (Universitas Palangka Raya, 2023)
The general objective of this research is to describe the phenomenon of code mixing in the student community at the Lamandau Dormitory. The specific objectives of this research are: (1) to describe the form of code-mixing at the word level in the conversations of the Lamandau dormitory student community. (2) to describe the form of code mixing at the phrase level in the conversation of the Lamandau dormitory student community. (3) to describe the form of code mixing at the clause level in the conversation of the Lamandau dormitory student community. (4) describe the implications of code mixing in learning short stories for class XI high school students. This research approach uses a qualitative research approach with descriptive methods. The source of the data in this study was the daily conversations of the student community at the Lamandau hostel. Data analysis in this study was carried out by collecting data identifying data, classifying data, and describing data. The results of this study indicate that (1) there is code mixing at the word level in the conversation of the student community at the Lamandau hostel. (2) there is code mixing at the phrase level in the conversations of the student community at the Lamandau hostel. (3) there is code mixing at the clause level in the conversations of the student community at the Lamandau dormitory. (4) the results of this study are used in learning short stories in class XI SMA, especially competency 4.9.